1991
DOI: 10.1002/hlca.19910740320
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐Salt Effects in Peptide Synthesis. Part II. Improvement of Degree of Resin Swelling and of Efficiency of Coupling in Solid‐Phase Synthesis

Abstract: The course of solid-phase peptide-coupling reactions as well as the swelling properties of a peptide-resin are influenced by the addition of inorganic salts (LiCI, LiBr, LiCIO,, KSCN). Used as additives, these salts can i ) improve coupling yields (e.g., for Fmoc-(Ala),-Phe-resin+ Fmoc-(Ala)6-Phe-resin in DMF/CH2C12 1 : 1 from 89.4 to 97.1 % (for poly(ethy1ene oxide) on polystyrene ( = PEO-PS) resin) or from 77.5 to 93.8% (for poly-( N , N'-dimethylacrylamide) on 'Kieselgur' ( = PDMAA-KG) resin) without and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The fourth hypothesis is that the coupling reaction for steps a and c was incomplete due to aggregation of the growing chain. Few conditions to overcome this potential problem of aggregation were evaluated including (1) reducing the loading density on the resin, i.e., the targeted loading of the resin with the first phenylalanine residue was half (Table , entry 5; Figure S4, entry 5, Supporting Information), (2) improving the solvation of the growing chain by either adding dichloromethane, i.e., 1/1 DMF/CH 2 Cl 2 (Table , entry 6; Figure S4, entry 6, Supporting Information), as CH 2 Cl 2 has a superior capacity to swell the resin as compared to DMF, or adding chaotropic salts such as lithium chloride (Table , entry 7; Figure S4, entry 7, Supporting Information), (3) conducting steps a and c under microwave irradiations (Table , entry 8; Figure S4, entry 8, Supporting Information), or (4) using a Tentagel resin (Table , entry 9; Figure S4, entry 9, Supporting Information) that is reported to have a kinetic behavior of its reactive sites similar to those in solution chemistry. None of the attempts conducted to noticeable positive changes.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth hypothesis is that the coupling reaction for steps a and c was incomplete due to aggregation of the growing chain. Few conditions to overcome this potential problem of aggregation were evaluated including (1) reducing the loading density on the resin, i.e., the targeted loading of the resin with the first phenylalanine residue was half (Table , entry 5; Figure S4, entry 5, Supporting Information), (2) improving the solvation of the growing chain by either adding dichloromethane, i.e., 1/1 DMF/CH 2 Cl 2 (Table , entry 6; Figure S4, entry 6, Supporting Information), as CH 2 Cl 2 has a superior capacity to swell the resin as compared to DMF, or adding chaotropic salts such as lithium chloride (Table , entry 7; Figure S4, entry 7, Supporting Information), (3) conducting steps a and c under microwave irradiations (Table , entry 8; Figure S4, entry 8, Supporting Information), or (4) using a Tentagel resin (Table , entry 9; Figure S4, entry 9, Supporting Information) that is reported to have a kinetic behavior of its reactive sites similar to those in solution chemistry. None of the attempts conducted to noticeable positive changes.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, anhydrous solvents such as DMF, NMP, and THF, or the binary mixture DMF/DCM (1 : 1), containing or not LiCl, LiBr, KSCN, or NaClO 4 , were employed in solid-phase coupling reactions starting from Fmoc-(Ala) 5 Phe, a wellknown difficult peptide sequence, on polystyrene, poly(N,N-dimethylacrylamide) kieselguhr (PDMAA-KG), and poly(ethylene oxide) (PEO)-PS resins. The results obtained indicated that the reaction yields were mainly enhanced in the presence of the lithium salts due to swelling enhancement of the peptide-resins [113].…”
Section: Use Of Chaotropic Salts During Peptide Chain Assemblymentioning
confidence: 99%
“…In most cases the target molecule is almost impossible to be isolated. The use of polar solvents (DMF, 25% DMSO in DMF v/v) [37][38][39], chaotropic salts (like 0.8 M NaClO 4 or LiCl or 4 M KSCN in DMF) before coupling [40], neutralization in situ in the Boc chemistry solid phase peptide synthesis [35,41,42], capping procedures [43][44][45], and N,O-bis-Fmoc-amino acid 2hydroxy-4-methoxybenzyl (Hmb) derivatives [46][47][48][49][50] are some of the approaches which were introduced in order to improve efficiency of the stepwise chemical synthesis of proteins. This causes lower reaction rates and therefore low coupling yields.…”
Section: Stepwise Solid Phase Synthesis Of Proteins and Protein-like mentioning
confidence: 99%